Investigating the Impact of Using Fiction Podcasts on Enhancing Students’ Listening Skill The Case of Second-Year LMD Students of English at the University of Souk-Ahras - DJEMAI Roumaissa (My University, 2024)
Abstract This research investigates the impact of incorporating fiction podcasts into an EFL education to improve second-year students’ listening skill at Mohammed Cherif Messaadia University in Souk Ahras. The data collection tools of this experimental research included a survey and a true experiment, with both qualitative and quantitative methods. The study involved sixty randomly selected students divided into control and experimental groups. The findings indicated that fiction podcasts significantly enhanced listening skill, particularly in auditory comprehension, and listening for gist, specific information and detail; hence, supporting the study’s hypotheses. This research contributes to advancing language education practices by exploring multimedia tools’ potential, such as podcasts in general and fictional ones in particular, to improve listening skill, language acquisition and guide curriculum development ---------------------- الملخص يهدف هذا البحث إلى دراسة تأثير إدماج البودكاستات الخيالية في تعليم اللغة اإلنجليزية كلغة أجنبية لتحسين مهارة االستماع لدى طالب السنة الثانية في جامعة محمد الشريف مساعدية في سوق أهراس. تشمل أدوات جمع البيانات لهذا البحث التجريبي استبيانًا وتجربة حقيقية، مع استخدام أساليب نوعية وكمية. شملت الدراسة ستين طالبًا تم اختيارهم عشوائيًا وتقسيمهم إلى مجموعة تجريبية ومجموعة مرجعية. أظهرت النتائج أن البودكاستات الخيالية ساهمت بشكل كبير في تحسين مهارة االستماع، خاصة في فهم المحتوى السمعي واالستماع للفكرة الرئيسية والمعلومات الدقيقة؛ مما يدعم فرضيات الدراسة. تسهم هذه الدراسة في تطوير ممارسات التعليم اللغوي من خالل استكشاف إمكانيات الوسائط المتعددة، مثل البودكاستات بشكل عام والخيالية منها بشكل خاص، في تحسين مهارة االستماع واكتساب اللغة وتوجيه تطور المناهج ---------------------- Résumé Cette recherche étudie l'impact de l'incorporation de podcasts de fiction dans l'enseignement de l'anglais langue étrangère (EFL) pour améliorer les compétences d'écoute des étudiants de deuxième année à l'Université Mohammed Cherif Messaadia de Souk Ahras. Les outils de collecte de données de cette recherche expérimentale comprenaient une enquête et une expérience réelle, utilisant à la fois des méthodes qualitatives et quantitatives. L'étude a impliqué soixante étudiants sélectionnés de manière aléatoire et répartis en groupes témoins et expérimentaux. Les résultats ont indiqué que les podcasts de fiction ont considérablement amélioré la compétence d'écoute, en particulier la compréhension auditive, l'écoute pour l'essentiel, les informations spécifiques et les détails ; soutenant ainsi les hypothèses de l'étude. Cette recherche contribue à faire progresser les pratiques en matière d'éducation linguistique en explorant le potentiel des outils multimédias, tels que les podcasts en général et les podcasts fictifs en particulier, pour améliorer les compétences d'écoute, l'acquisition linguistique et guider le développement des programmes.